Identifikasi Letak Buku di Perpustakaan Universitas Prima Indonesia Menggunakan Metode FP-Growth - Satriandi, Satriandi (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
This research uses the FP-Growth method to identify the location of books in the Prima Indonesia University library with the following steps: (1) conducting research, (2) solving the problem, (3) studying the literature, (4) inputting data, (5) analyzing high frequency patterns, determining associative rules, and making conclusions. This research aims to apply the FP-Growth method to arrange book layouts according to needs. This research aims to: (1) apply the FP-Growth method to arrange the layout of books according to needs, (2) implement the FP-Growth method to arrange the layout of books in the Prima Indonesia University (UNPRI) library, and (3) create an application using language and a data base with the FP-Growth method which can arrange the layout of library books. The result of the research is that using the FP-Growth method book searches can be faster with a success rate of 80%, making it easier to get the book you want.